Acute Safety and Efficacy of a Novel Multipolar Irrigated Radiofrequency Ablation Catheter for Pulmonary Vein Isolation. (4th December 2013) - DENEKE, THOMAS; SCHADE, ANJA; MÜLLER, PATRICK; SCHMITT, RAINER; CHRISTOPOULOS, GEORGIOS; KRUG, JOACHIM; SZÖLLÖSI, GEZA; MÜGGE, ANDREAS; KERBER, SEBASTIAN; NENTWICH, KARIN
<x xml:space="preserve">Abstract</x> Introduction "Single shot" ablation devices to treat symptomatic atrial fibrillation have been engineered over the last years. Safety and efficacy also includes subclinical complications only detected with esophageal endoscopy or cerebral MRI in asymptomatic patients. We studied the acute efficacy and safety profile of a novel multipolar irrigated RF ablation catheter (nMARQ™). Methods and Results Forty‐three patients underwent pulmonary vein isolation (PVI) using the novel ablation device. Patient baseline and procedural characteristics were documented. Efficacy of PVI was identified using only the nMARQ™ catheter. All patients underwent postablation endoscopic evaluation of the esophagus to document thermal damage and cerebral MRI (diffusion weight imaging, attenuated diffusion coefficient‐map) to document incidence and number of silent cerebral lesions (SCL). Effective PVI was achieved in 98% of targeted PVs in a mean procedure time of 133 minutes. A mean of 4.8, 60‐second RF applications, per PV was needed for effective PVI. No clinical procedure‐associated complications were noted. Esophageal temperature increase >40.5 °C was noted in 22 (51%) patients and 14 of these had thermal esophageal lesions on endoscopic evaluation. A total of 26 SCLs were noted in 14 patients (33%; 1.9/patient; mean diameter of 2.3 mm, 88% of lesions were ≤3 mm). Conclusions PVI using the novel irrigated RF multipolar ablation device (nMARQ™) appears to be acutely effective. No clinical complications were identified. A high incidence of SCL (33%) and thermal esophageal lesions (33%) bears caution and further studies on long‐term efficacy and safety are needed.